Cesarean Delivery in a Case of Persistent Second Trimester Ovarian Hyperstimulation Syndrome - Torky, Haitham Atef (Zeitschrift für Geburtshilfe und Neonatologie, 2017)
Background Ovarian hyperstimulation syndrome develops as an iatrogenic complication related to ovulation induction. It is usually self-limiting with complete resolution expected within 10–14 days.Case The current case is a report of an unusually prolonged course of ovarian hyperstimulation syndrome persisting until 22 weeks of gestation, accidentally discovered and managed by cesarean section due to an obstetric indication.Conclusion Clinicians should be aware of this possibility when managing cases of IVF pregnancy.